Mechanistic insight into potential toxic effects of microplastics and nanoplastics on human health - Charu Thapliyal; Sonali Negi; Sakshi Nagarkoti; Achlesh Daverey (Discover Applied Sciences)
Abstract Microplastics and nanoplastics (MNPs) have gained attention as pervasive environmental pollutants that pose a risk to human health. This review provides comprehensive and updated scientific information on how MNPs enter the human body through multiple routes such as inhalation, ingestion, and dermal contact, and circulate through the bloodstream to get deposited in various organs. Its focus revolves around the toxicological effects caused by MNPs on human health, specifically on vital organ systems such as the respiratory, gastrointestinal, cardiovascular, nervous, immune, reproductive, endocrine, and urinary systems. Important findings indicate that MNP exposure may result in oxidative stress (OS), inflammation, impaired biochemical and energy metabolism, altered morphology and proliferation, diminished cellular metabolic activity, immune dysfunction, cytotoxicity, genotoxicity, disrupted microbial metabolic pathways, developmental abnormalities, and carcinogenicity. The toxicological effects of MNPs depend upon many factors such as their size, type, concentration, and charge. The review has also highlighted the knowledge gaps in current research. Despite evidence from cellular and animal studies, human studies on the toxic effects of MNPs are limited. Most research has been conducted on specific types of MNPs, however, limited scientific information is available on many commonly used environmental MNPs. Future research should investigate the MNP exposure by considering realistic doses, concentration-dependent toxicological effects, and quantification of its harmful outcomes. This necessitates larger sample sizes and robust analytical techniques to completely comprehend the true toxicological consequences of MNPs on human health.